Removing linear phase mismatches in concatenative speech synthesis. - Stylianou, Y.
Many current text-to-speech (TTS) systems are based on the concatenation of acoustic units of recorded speech. While this approach is believed to lead to higher intelligibility and naturalness than synthesis-by-rule, it has to cope with the issues of concatenating acoustic units that have been recorded at different times and in a different order. One important issue related to the concatenation of these acoustic units is their synchronization. In terms of signal processing this means removing linear phase mismatches between concatenated speech frames. This paper presents two novel approaches to the problem of synchronization of speech frames with an application to concatenative speech synthesis. Both methods are based on the processing of phase spectra without, however, decreasing the quality of the output speech, in contrast to previously proposed methods. The first method is based on the notion of center of gravity and the second on differentiated phase data. They are applied off-line, during the preparation of the speech database without, therefore, any computational burden on synthesis. The proposed methods have been tested with the harmonic plus noise model, HNM, and the TTS system of AT&T Labs. The resulting synthetic speech is free of linear phase mismatches
Keywords: AT&T Labs; HNM; TTS system; Acoustic units concatenation; Center of gravity; Concatenated speech frames; Concatenative speech synthesis; Differentiated phase data; Harmonic plus noise model; Linear phase mismatch removal; Output speech quality; Phase spectra processing; Recorded speech; Signal processing; Speech database; Speech intelligibility; Synchronization; Text-to-speech systems